Self-assembled quantum structures deposited by molecular beam epitaxy on GaAs (100) and (311)A substrates - Hahn, CK; Kim, EK; Jeun, IS; Kim, KM; Kim, MS; Min, SK; Park, JH (KOREAN PHYSICAL SOC, 1996)
In0.5Ga0.5As quantum wires (QWR) and quantum dots (QD) are formed directly on GaAs (311)A and (100) substrates by the molecular beam epitaxy (MBE) technique. The growth mode transition from a 2-dimensional to a 3-dimensional structure is confirmed by the reflection high energy electron diffraction (RHEED) method. Atomic force microscopy (AFM) reveals that the base width of the QWR grown on GaAs(100) substrate is about 20 similar to 25 nm, which is about 5 nm smaller than that of the QWR grown on GaAs (311)A under the same growth conditions. Also, QD structures are grown on GaAs(100) substrates. The optical properties of the quantum dot structures are observed with photoluminescence(PL) measurements and the PL peaks of the QD's are detected at 1.251 eV and 1.326 eV.
Keywords: GROWTH; PHOTOLUMINESCENCE; FABRICATION